THE FAMILY BODY AND OWN BODY: INTERT EXTUAL PATHS BETWEEN CéSAR VALLEJO AND JOSÉ WATA NABE - Malpartida, Miguel (2012)
This article explores the pragmatic, thematic and allegorical convergences in texts linked to the family environment, diseases, and body auscultation in the poetry of César Vallejo and José Watanabe. This is shown through common allegories courses such as those of the navel and those of the belly, as well as through Watanabe’s rewriting of Vallejo’s traditional corporal images with the purpose of addressing the identity and confidence in the body. Also, we can see a transit, common to both creators between the family body, linked to the disease, and one’s own body, source of health and transcendence.